PENYULUHAN PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) DI MASJID DARUL MUTTAQIN KOTA PADANG - Suharni Suharni; Erdanella Setiawati; Rosmaini Rosmaini; Rendri Bayu Hansah; Yanti Fitri Yasa; Shafira Larissa; Muhammad Alfan Syuri Asqa; Relly Angelica Putriz; Sahla Riska Nafiah; Atika Karina Asmi; Gangga Mahatma (Yayasan Nusantara Hasana Berdikari, 2026)
Dengue Hemorrhagic Fever (DHF) is a public health problem in Indonesia, particularly during the rainy season when the population of Aedes aegypti mosquitoes increases. This report describes a household-based health promotion intervention conducted by students of the Faculty of Medicine, Baiturrahmah University. Community-based educational methods and pre- and post-test evaluations were used to improve public understanding of DHF prevention. The results showed a significant increase in participants’ knowledge scores, from an average of 70.6% to 83.7%. Alternative household-based educational strategies proved effective in increasing community awareness and engagement in mosquito breeding site eradication efforts. This activity also emphasized sustainability through cross-sector collaboration and a community-based approach.